2017
DOI: 10.1167/iovs.16-20241
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Therapeutic Tissue Crosslinking (TXL) for Myopia Using Second Harmonic Generation Signal Microscopy in Rabbit Sclera

Abstract: PurposeSecond harmonic generation signals (SHG) are emitted preferentially from collagenous tissue structures and have been used to evaluate photochemically-induced (CXL) crosslinking changes in the cornea. Since therapeutic tissue crosslinking (TXL) using sodium hydroxymethylglycinate (SMG) of the sclera is a potential treatment for high myopia, we explored the use of SHG microscopy to evaluate the effects.MethodsSingle sub-Tenon's (sT) injections (400 μL) using SMG (40–400 mM) were made at the equatorial 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Interestingly, however, while glyceraldehyde increases scleral stress and Young's modulus, as expected from cross-linking, it showed no significant effect in preventing myopia development (64). Other agents that have been investigated for enhancing scleral collagen cross-linking that may yet prove beneficial in preventing myopia development include methylglyoxal (65) and a range of formaldehyde releasers including sodium hydroxymethylglycinate (67,68).…”
Section: Collagen Cross-linkingmentioning
confidence: 99%
“…Interestingly, however, while glyceraldehyde increases scleral stress and Young's modulus, as expected from cross-linking, it showed no significant effect in preventing myopia development (64). Other agents that have been investigated for enhancing scleral collagen cross-linking that may yet prove beneficial in preventing myopia development include methylglyoxal (65) and a range of formaldehyde releasers including sodium hydroxymethylglycinate (67,68).…”
Section: Collagen Cross-linkingmentioning
confidence: 99%
“…have shown that a much lower concentration of genipin is required to achieve a comparable scleral stiffening effect using glyceraldehyde (7 fold) or methylglyoxal (30 fold), which are alternative low‐cytotoxic collagen crosslinking agents. Recently, SXL was shown to reduce collagen fibril crimping, supporting the notion that SXL can counteract biomechanical and micro‐structural changes in the sclera during myopia . Only one study has investigated the biomechanics of the sclera in animal eyes with induced myopia and after SXL .…”
Section: Introductionmentioning
confidence: 97%
“…This report is the first of using SMG in live animal corneas; the previous literature regarding this compound has been carried out in ex vivo systems. 7 , 8 SMG is a compound from a class of compounds known as formaldehyde-releasing agents (FARs). FARs are in widespread use as chemical preservatives in cosmetics and other personal care products, such as shampoos and conditioners.…”
Section: Introductionmentioning
confidence: 99%